Manufacturing technology - Timings, R. L. (Roger Leslie) (Harlow : Longman, 1998)
This is an updated and expanded edition of R.L. Timings' comprehensive introduction to the principles and practice of engineering manufacturing processes
Also issued online
Keywords: Manufacturing processes; Production engineering; Technological innovations